Zero-defect program in aerospace manufacturing to reduce repetitive customer complaint wrong part mark issues - Baseri, Nor Afifah (2024)
One of the aerospace companies located in Malacca implement a ZDP to reduce repetitive customer issues in their company. To reduce repetitive customer complaints in an aerospace company, the implementation of a ZDP is crucial because Zero-defect manufacturing aims to achieve defect-free production through continuous improvement, ultimately enhancing customer satisfaction and reducing waste.In 2022, the aerospace company experienced a significant number of repeated consumer complaints. Ensuring consumer satisfaction is important for the long-term profitability and viability of the company. The repeated occurrence of problems in customer complaints is a major barrier to delivering a satisfactory customer experience. In the aerospace industry, communication channels regarding corrective actions are often fragmented, hindering the efficient exchange of information between different departments or teams. This lack of integrated communication impedes the dissemination of insights gained from resolving specific incidents, limiting the organization's ability to implement comprehensive and systemic changes. The Pareto chart identifies the primary customer complaint concern as the Wrong Part Mark. By analyzing the Pareto chart, researchers can thoroughly examine which customer are responsible for the issue of the wrong part mark. This analysis reveals that there is a repeated customer complaint connected with these projects, the obejective of this study to design the Customer Complaint database management system for customer complaint issue and then to replicate corrective actions across different programs within the company. Lastly to verify implementation of corrective actions into the relevant project or process. The 8D methodology provides a structured framework with eight disciplines, each having specific tasks and goals to effectively recognize, rectify, and prevent issues. This method is widely used to handle quality and continuous improvement efforts in various industries, including aerospace, automotive, and manufacturing. Recent study has showcased how the 8D methodology is applied to address manufacturing defects and cut down on customer complaints. Lastly, to makes sure the action is implemented in production floor, Gemba at production floor shall be conduct when the action closed. Grmba activity lead by QA personnel and support by committee. The Customer Complaint Zero Defect Program (CQ-ZDP) resulted in a clear reduction in repetitive customer complaints, with a 4% decrease from 2021 to early 2024. By systematically addressing the root causes of these issues through the 8D methodology, the aerospace company significantly improved product quality, as evidenced by the decrease in part marking issues. This success highlights the importance of a proactive and structured approach to defect management, which not only resolves immediate issues but also prevents their recurrence.